THE IMPLEMENTATION OF PROBLEM SOLVING STRATE-GY TO THE MIDWIFERY STUDENTS IN AKADEMI KE-BIDANAN PANCA BAKTI - Kristina Laora (Jurnal Ilmiah Spectral, 2019)
ESL students always encounter the issue of solving complicated problems in learning English. Various problem may occur during the learning process including speaking, listening, writing and reading. The most complicated issues are often faced by the students who learn English for the specific purpose for instance English for law, English for tourism, English for business or English for medical purpose. The prob-lems may dealing with types of expression, vocabularies, standard and formal struc-tures that will be used most of all in a specific field. This purpose of this study was to implement the problem solution strategy in the medical field especially for midwifery students in Akademi Kebidanan Panca Bakti Pontianak. The midwifery students were trained to be able to solve the problems regarding with the health issues. This study constitute an attempt to identify the common problems and how to solve by us-ing problem solution strategy. The most common issues found were dealing with terminologies and the risk signs during pregnancy. The result showed that by using problem solution strategy, students were successful in solving the health problems. They were able elaborate the way how to deal with the health sign during pregnancy for instance the risk sign dealing with weighing the mother, the risk sign if a mother has a high fever, the risk sign if a mother has a high blood pressure, the risk sign if a mother has an abnormal pulse rate and the risk sign if a mother grows fast or slowly. By understanding how to solve the problems, the midwifery students will be more professional.